2019
DOI: 10.1177/1040638719843171
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma spp. in dairy ruminants in Jordan: high individual and herd-level seroprevalence and association with abortions

Abstract: We estimated the seroprevalence of, and associated risk factors for, anaplasmosis in dairy cows, sheep, and goats in all regions of Jordan. Apparently healthy animals from 135 farms (31 cow, 68 sheep, and 36 goat farms) were tested for Anaplasma spp. antibodies by a competitive ELISA. At the farm level, 36%, 94%, and 94% of cow, sheep, and goat farms, respectively, were seropositive for Anaplasma spp. At the individual animal level, 22%, 89%, and 82% of the tested cows, sheep, and goats, respectively, were ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…The current study showed that goat farmers use open lands for grazing with minimal grazing in the highlands regions. Similarly to the findings by J o r d a n [47], the difference in herd management could expose small ruminants to greater tick numbers and could explain the higher seroprevalence in goats. Grazing goats showed higher seropositivity compared to those who remain in permanent housing and this can be explained by the fact that grazing systems may increase the risk of getting vector ticks and enhance the risk of anaplasma infections [31].…”
Section: Comparative Study Of the Two Methods (Mgg And Celisa)supporting
confidence: 53%
See 1 more Smart Citation
“…The current study showed that goat farmers use open lands for grazing with minimal grazing in the highlands regions. Similarly to the findings by J o r d a n [47], the difference in herd management could expose small ruminants to greater tick numbers and could explain the higher seroprevalence in goats. Grazing goats showed higher seropositivity compared to those who remain in permanent housing and this can be explained by the fact that grazing systems may increase the risk of getting vector ticks and enhance the risk of anaplasma infections [31].…”
Section: Comparative Study Of the Two Methods (Mgg And Celisa)supporting
confidence: 53%
“…Grazing goats showed higher seropositivity compared to those who remain in permanent housing and this can be explained by the fact that grazing systems may increase the risk of getting vector ticks and enhance the risk of anaplasma infections [31]. A higher seroprevalence was demonstrated for the extensive system infection such as described in Jordan [47,48]. Anaplasma spp.…”
Section: Comparative Study Of the Two Methods (Mgg And Celisa)mentioning
confidence: 99%
“…For goats, the seroprevalence rate is consistent with the previous seroprevalence rate observed in Pakistan (25%) [ 8 ], while it was lower than the seroprevalence rate estimated in Botswana (88%) [ 33 ] and Jordan (82%) [ 34 ]. However, the difference between seroprevalence rates in these countries could be due to variations of several factors such as the sampling process, the number of examined animals, the bioclimate, and the kind of tests used [ 27 , 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…The seroprevalence at farm level was estimated at 36%, 94% and 94% for cow, sheep and goat farms, as well as at animal level, with 22% for cattle, 89% for sheep and 82% for goats (66). Detection of A. phagocytophilum in non-ruminant hosts varies: carcasses of stray dogs showed 39.5% A. phagocytophilum-positive samples when examined by species-specific PCR (86) but 9.9% of dogs (pet, stray, working) were found to be seropositive in different areas of Jordan, such as Amman, Jarash, Irbid, Ajloun and the northern Jordan Valley (Table III) (87).…”
Section: Jordanmentioning
confidence: 99%